PENGARUH PROMOSI PENJUALAN (SALES PROMOTION) DAN BELANJA HEDONIS (HEDONIC SHOPPING) TERHADAP IMPULSE BUYING SECARA ONLINE - Sakdiah Diah; Cut Sukmawati (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
This study aims to see how the influence of sales promotion and hedonic shopping on impulse buying online on Shopee consumers, Fisip students, Malikussaleh University. This study uses descriptive quantitative research using proportional stratified random sampling obtained 100 respondents as research samples. Data was collected by survey method. Analysis of the data used in this study using multiple linear regression with the help of the SPSS 25.0 software program. The results of the study indicate that the sales promotion variable partially has no positive and significant effect on impulse buying with a significance value of 0.859 > 0.05. However, the hedonic shopping variable has a positive and significant effect with a significance value of 0.000 < 0.05. Meanwhile, simultaneously sales promotion and hedonic shopping have a positive and significant effect on impulse buying with a calculated F value greater than F table (56.766 > 3.09) with a significance level of (0.000 < 0.05).